Evidence of ameliorated Middle Weichselian climate and sub‐arctic environment in the western Baltic region: coring lake sediments at Klintholm, Møn, Denmark. (30th December 2015) - Houmark‐Nielsen, Michael; Bennike, Ole; Lemdahl, Geoffrey; Lüthgens, Christopher
Abstract : Coring through glaciotectonically stacked Quaternary sediments situated below sea level on the island of Møn, Denmark, recovered a succession of interstadial sediments of Middle Weichselian age. Plant and animal remains including insects found in laminated sand and mud indicate deposition in a lake surrounded by dwarf shrubs, herbs, mosses and rare trees. The insect fauna indicates a mean July temperature of 8–12 °C, suggesting an arctic to sub‐arctic environment, while winter temperatures around −8 to −22 °C suggest periglacial conditions with permafrost. Luminescence dating of sediment samples gave ages from 48–29 ka, and radiocarbon dating indicates deposition of plant fragments between 45 and 36 ka BP. The fossil assemblage from Møn shows close resemblance to those from other sites with similar ages found in the vicinity of the western Baltic Basin.